Napabucasin Plus FOLFIRI in Patients With Previously Treated Metastatic Colorectal Cancer: Results From the Open-Label, Randomized Phase III CanStem303C Study - Shah, Manish A; Yoshino, Takayuki; Tebbutt, Niall C; Grothey, Axel; Tabernero, Josep; Xu, Rui-Hua; Cervantes, Andres; Oh, Sang Cheul; Yamaguchi, Kensei; Fakih, Marwan; Falcone, Alfredo; Wu, Christina; et al. (Clinical colorectal cancer, 2023)
PURPOSE: Napabucasin is an investigational, orally administered reactive oxygen species generator bioactivated by intracellular antioxidant NAD(P)H:quinone oxidoreductase 1 that has been evaluated in various solid tumors, including metastatic colorectal cancer (mCRC). Phosphorylated signal transducer and activator of transcription 3 (pSTAT3) is hypothesized to predict response in napabucasin-treated patients with mCRC. PATIENT AND METHODS: In the multi-center, open-label, phase III CanStem303C (NCT02753127) study, adults with histologically confirmed mCRC that progressed on first-line fluoropyrimidine plus oxaliplatin ± bevacizumab were randomized to twice-daily napabucasin plus FOLFIRI (napabucasin) or FOLFIRI alone (control). The primary endpoint was overall survival (OS) in the general study population and in patients with pSTAT3-positive tumors (biomarker-positive). RESULTS: In the general study population (napabucasin, n = 624; control, n = 629), median OS was 14.3 months for napabucasin and 13.8 months for control (hazard ratio [HR], 0.976, one-sided P = .74). Overall, 44% of patients were biomarker-positive (napabucasin, n = 275; control, n = 272). In the biomarker-positive population, median OS was 13.2 months for napabucasin and 12.1 months for control (HR, 0.969; one-sided P > .99). In the control arm, median OS was shorter for biomarker-positive versus biomarker negative patients (12.1 vs. 18.5 months; HR, 1.518; nominal 2-sided P = .0002). The most common treatment-emergent adverse events (TEAEs) were diarrhea (napabucasin, 84.6%; control, 53.9%), nausea (60.5%, 50.5%), vomiting (41.2%, 29.3%), and abdominal pain (41.0%, 25.2%). Grade ≥3 TEAEs occurred in 73.8% of napabucasin-treated and 66.7% of control-treated patients, most commonly diarrhea (21.2%, 7.0%), neutrophil count decreased (13.7%, 19.2%), and neutropenia (13.3%, 15.2%). Safety was similar in biomarker-positive patients. CONCLUSION: In patients with previously treated mCRC, adding napabucasin to FOLFIRI did not improve OS. Results from the control arm indicate that pSTAT3 is an adverse prognostic factor in mCRC.
Keywords: kolorektální nádory; fluoruracil; Fluorouracil; kamptothecin; Colorectal Neoplasms; Camptothecin; Adult; bevacizumab; nádory tračníku; nádory rekta; Humans; Leucovorin; leukovorin; Colonic Neoplasms; Antineoplastic Combined Chemotherapy Protocols; Rectal Neoplasms; protokoly protinádorové kombinované chemoterapie; dospělí; lidé; Bevacizumab